The impact of race and gender on correctional officers' orientation to the integrated environment - Van Voorhis, Patricia; Cullen, Francis T.; Link, Bruce G.; Wolfe, Nancy Travis (Journal of research in crime and delinquency, 1991)
The effects of race and gender on the work experiences and professional orientations of correctional officers were tested using data obtained from 155 front-line staff in a southern U.S. correctional system. Main effect and interaction multivariate tests were conducted, and both organizational and individual effects were observed. Racial correlates showed that Black officers were significantly more likely to perceive peer support, to perceive their job as dangerous, and to espouse a rehabilitation orientation. Gender was correlated only with supervisory support. Two organizational correlates were found. The first, maximum security placement, adversely affected officers' perceptions of danger and work stress but favorably affected their perceptions of peer support; the other, night shift, showed that workers on that shift were significantly more likely to have a custody orientation. Upon controlling for supervisory support and peer support, R2 values increased for job dissatisfaction, work stress, and role conflict regressions and race and gender effects emerged or became stronger. Specifically, Blacks were more likely to perceive their work as dangerous and dissatisfying and women were more likely to experience work stress. Interaction analysis revealed an interaction between race and peer support and between race and gender on perceptions of danger